2014
DOI: 10.1111/bju.12483
|View full text |Cite
|
Sign up to set email alerts
|

The impact of length and location of positive margins in predicting biochemical recurrence after robot-assisted radical prostatectomy with a minimum follow-up of 5 years

Abstract: Objective• To evaluate the role of positive surgical margin (PSM) size/focality and location in relation to risk of biochemical recurrence (BCR) after robot-assisted radical prostatectomy (RARP). Patients and Methods• Clinicopathological data were collected from 904 patients who underwent RARP at a single European institution from 2002 to 2006. • PSM status after RARP was defined as cancer cells at the inked margin, and was stratified by size/focality and location.• The outcome variable was BCR, defined as a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
56
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 63 publications
(64 citation statements)
references
References 42 publications
(46 reference statements)
6
56
0
Order By: Relevance
“…However, over half of the patients with RM1 did not experience BCR at 4 years in this study using the BCR threshold of 0.2 ng/ml. This result was comparable with that of previous reports (4,7,8). Recently, Toussi et al…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…However, over half of the patients with RM1 did not experience BCR at 4 years in this study using the BCR threshold of 0.2 ng/ml. This result was comparable with that of previous reports (4,7,8). Recently, Toussi et al…”
Section: Discussionsupporting
confidence: 93%
“…Thus, patients with RM1 are candidates for immediate adjuvant radiation therapy (RT) to decrease BCR and provide a survival benefit compared with that of patients undergoing observation (10)(11)(12). However, several reports indicated that BCR did not occur in over half of the patients, even in the presence of RM1, over 5-year follow-up (4,7,8). This raises an issue for the treatment of patients with RM1 in which a number of patients are overtreated by immediate adjuvant RT.…”
Section: Introductionmentioning
confidence: 99%
“…Each institution involved in this study have reported their method of RARP, which has been detailed previously [11,16,17]. Subsequent subtle modifications are used by some of the contributing centers but not others (e.g., grades of nerve-sparing dissection, cautery-free technique, local hypothermia, and retrograde dissection) [18][19][20].…”
Section: Surgical Techniquementioning
confidence: 99%
“…Tissue handling, retraction, and tension applied at each step are all unique from open radical (ORP) and laparoscopic radical prostatectomy procedures; hence, the effect of margin parameters on outcomes after robotic-assisted radical prostatectomy (RARP) cannot be drawn from such studies. Two recent RARP single-institution series have been published; one establishing the effect of PSMs Z3 mm or multifocal margins compared with those o3 mm or unifocal margins (hazard ratio [HR] = 2.84, 95% CI: 1.76-4.59) [10,11]. This effect has not been demonstrated in RARP multiinstitutional cohorts with long-term follow-up.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation